Analysis of Consumer Preferences for Souvenir Design Needs in Pangandaran Tourist Attractions - Moh Wildan Lesmana; Atikah Nurhayati; Asep Agus Handaka Suryana; Wahyuniar Pamungkas; Donny Juliandri Prihadi (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: The purpose of this research is to analyze consumer preferences in choosing souvenirs and produce souvenir design recommendations that can improve the quality of consumer experience at Pangandaran tourist attractions. Method: The method used in this research uses a mix method between qualitative and quantitative. The data collected using the survey method by distributing questionnaires to 30 respondents with purposive sampling technique. Respondents are 30 people who have shopped for souvenirs in Pangandaran. Primary data obtained through the survey method is then processed using the SPSS analysis tool using variable and hypothesis test analysis techniques, validity and reliability tests, T tests, and finally the determination coefficient test. Result: Based on the data that has been processed using the SPSS software analysis tool with the T test analysis technique, it results that the hypothesis of natural and cultural beauty variables has significance to the need for souvenir design in Pangandaran because the Sig value. <0.05, which means Ho is rejected and Ha is accepted, while the variable pangandaran writing, simple design, and bright colors are not significant to the need for souvenir design in pangandaran because the Sig value> 0.05 which means Ho is accepted and Ha is rejected. In the coefficient of determination test, the correlation coefficient value is 0.769, indicating that the interpretation of the value is within the numbers 0.5 to 0.75. It can be concluded that the souvenir design variable has a strong relationship with souvenir design needs in Pangandaran. Contribution: This research is expected to be a reference for research that will be conducted in the tourism industry, especially on consumer preferences and contribute to the development of the local tourism industry by providing souvenir products that are unique and oriented to the needs of tourists.